Trypsin-treating attached cells - Morrey, John D; Lowry, William (Utah : Taped Technologies, 1992)
Described the techniques of trypsin treatment. The treatment include rinse with serum-free saline, add trypsin, neutralize trypsin, remove trypsin, add medium and disperse cells
Copy available in DVD format
Keywords: Trypsin; Cells